Identifikasi Pseudomonas aeruginosa dan tes sensitivitas siprofloksasin pada abses periodontal Identification of Pseudomonas aeruginosa and sensitivity test of ciprofloxacin on periodontal abcess - Irene E. Rieuwpassa; Muliaty Yunus; I Wayan Suka Arsana (DiscoverSys Inc., 2011)
Periodontitis is a common type of periodontal disease caused by expansion of the early stages of gingivalinflammation. Expansion of inflammation to the tissue structures supporting the teeth can be modified by thepathogenic ability of plaque or host resistance factors. A total of 200 different bacteria have been identified on theplaque. Resistance to antimicrobials can be natural because the microbes develop mechanisms to defendthemselves. Ciprofloxacin is a synthetic drug of the second generation quinolones derivatives. Mechanism of itsaction is to inhibit the activity of bacterial DNA gyrase, which is bactericidal with a broad spectrum against Grampositiveor negative. This observational study identified P. aeruginosa and sensitivity test was performed tociprofloxacin in periodontal abscesses. Study conducted in 23 patients with periodontal abscess. Of those,Pseudomonas was acquired for 8 samples and 4 of them was resistant to ciprofloxacin.